Estrategias didácticas en la disortografía de los estudiantes del sexto grado A, en el área de Lengua y Literatura, de la Escuela de Educación Básica Dr. Reinaldo Espinosa Aguilar de Loja, período académico 2018 – 2019. Lineamientos alternativos - Ayala Tapìa, Leiver German (2019)
The present research called Didactic Strategies in the disortography of sixth grade A students, in the area of Language and Literature, of the School of Basic Education Dr. Reinaldo Espinosa Aguilar de Loja, academic period 2018 - 2019. Alternative guidelines It has as a general objective: To determine how the didactic strategies affect the disortography of sixth grade A students in the area of Language and Literature of the School of Basic Education Dr. Reinaldo Espinosa Aguilar academic period 2018 - 2019. The type of study is descriptive; nonexperimental design: observational, descriptive, inductive, deductive, hermeneutical, analytical, synthetic and statistical methods; the techniques: survey, test; instruments: written questionnaire, reading and writing learning test; diagnostic procedures, theoretical foundation, alternative guidelines approach; As a result it was found that the teacher does not apply teaching strategies in the teaching of spelling rules, which has led to students having dysortography problems, which complicates their learning. 32 students and the teacher participated in the research work. It is concluded that the application of teaching strategies in the teaching of spelling rules is an essential part of not falling into the problem of dysortography and thus students do not have difficulties when writing.